STUDI KASUS PERNIKAHAN DINI (EARLY AGE MARIAEGE) DI WILAYAH KERJA PUSKESMAS MATANGA KECAMATAN BANGGAI SELATAN KABUPATEN BANGGAI LAUT - Harto, Harto Yaakon; Syafar, Muhammad Syafar; Diana, Diana Mirja Togubu (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
Early Marriage is still a trending problem in Indonesia. Marriage is carried out under the age of 19, which is not in accordance with the provisions of the Marriage Law Number 16 of 2019 concerning marriage. The emergence of impacts and dangers due to early marriage and also the increasing cases prompted researchers to conduct this study. This study aims to find out in depth about children's knowledge, family roles, pre-prosperous economy and culture that encourage early marriage. This research method uses qualitative research with a Case Study Research approach, with a total of 9 (nine) informants. The selection of informants was determined by the purposive sampling technique. Data collection was obtained through interviews, observations and observations. Data analysis was conducted qualitatively. The results of the study showed that low informant knowledge, the role of parents, and a pre-prosperous economy encouraged early marriage. Culture does not play a role in the occurrence of early marriage. The habit of molibai (women living in a man's house before a proposal or legal marriage) is not part of a cultural tradition, but a past habit that does not apply in today's era. The conclusion of this study is that good children's knowledge is very important, especially in making good decisions regarding marriage for a good future. The role of parents is needed to think well before marrying off children. Empowerment and improvement of the family economy are very basic things to pay attention to, access to information through education, cross-sector socialization for children and families to prevent early marriage.